(untitled) (Al-Qamar, 2022)
Islam is a complete and comprehensive code of life. All the problems of life are covered by its teachings. Islam does not leave a person alone at any point of life, rather it guides him completely. However, the rules of Islam are of two types: (1)Mansoos : The clear solution of which is in the Quran and Sunnah. (2)Ghair Mansoos: the Clear solution of which is not in the Qur’an and Sunnah. The principle of Itehad is applied to the second type of solution. Analogy (Qiyas) is one of these sources. Through qiyas unspecified problems are solved. Qiyas is the fourth important source of Islamic Shariah. It enjoys paramount status after the Holy Quaran,Hadith and Ijma e Umah. Qiyas literally means destiny,the term Analogy on the Basis of common causation ,and issuance of Mansoos order in ghair mansoos،order , or issuing a command clearly stated in the Quran and sunnah and something that doesn’t have a command in Quran and sunnah,or drawing a comparison in order to show similarities in some aspects .For this very reason ,the teachings not found in the Quran ,sunnah and ajmah can be found in Qiyas. So, in this regard, nobody is allowed to do qiyas in matters of religion, it requires high qualifications. That ability is the name of strong access to the Qur’an and Sunnah, those who have these qualifications, are actually mujtahids and a common man who is not well versed in Sharia is not entitled to do Qiyas in this matter.